Morāles un politiskās problēmas Džozefa O` Konnora romānā „Jūras zvaigzne” - Ostrovska, Viktorija (Latvijas Universitāte, 2013)
Maģistra darbs ir veltīts mūsdienu īru rakstnieka Džozefa O’Konnora vēsturiskajam romānam „Jūras zvaigzne”. Darba mērķis ir parādīt, kādas morāles un politiskās problēmas autors saista ar šo Īrijas un Lielbritānijas vēstures traģisko lappusi un cik tās ir nozīmīgas šodien. Pētījuma rezultāti parāda ka Džozefa O’Konnora romāns „Jūras zvaigzne” pieder vēsturiskā romāna žanram un ka romānā izvirzītās problēmas nav zaudējušas savu nozīmi arī mūsdienās. Atslēgvārdi: vēsture, vēsturiskais romāns, Džozefs O’Konnors, Īrija, Lielbritānija, Lielais Īrijas bads.

The present Master Thesis aims at the clarification of moral and political anxieties of the novel “Star of the Sea”. “Star of the Sea” by Joseph O’Connor is the example of modern historical novel focusing on the Victorian Ireland, and, particularly, the Great Irish Famine. The novel is based on real historical setting and events. The work presents the information on the problems the novel raises and on their topicality nowadays. The main results of the research showed that Joseph O’Connor presented the readers several important issues which touch upon both, moral and political levels of the lives of Irish and British people. “Star of the Sea” can be viewed and analyzed as a literary work belonging to the genre of historical novel. Key words: history, historical novel, Joseph O’Connor, Ireland, Britain, Great Irish Famine.
Moral un Political Anxieties in Joseph O`Connor`s Novel "Star of the Sea"
Keywords: Valodniecība